Reversion of tumor hepatocytes to normal hepatocytes during liver tumor regression in an oncogene-expressing transgenic zebrafish model - Yan Li; Ira Agrawal; Zhiyuan Gong (The Company of Biologists, 2019)
Tumors are frequently dependent on primary oncogenes to maintain their malignant properties (known as 'oncogene addiction'). We have previously established several inducible hepatocellular carcinoma (HCC) models in zebrafish by transgenic expression of an oncogene. These tumor models are strongly oncogene addicted, as the induced and histologically proven liver tumors regress after suppression of oncogene expression by removal of a chemical inducer. However, the question of whether the liver tumor cells are eliminated or revert to normal cells remains unanswered. In the present study, we generated a novel Cre/loxP transgenic zebrafish line, Tg(fabp10: loxP-EGFP-stop-loxP-DsRed; TRE: CreERT2) (abbreviated to CreER), in order to trace tumor cell lineage during tumor regression after crossing with the xmrk (activated EGFR homolog) oncogene transgenic line, Tg(fabp10: rtTA; TRE: xmrk; krt4: EGFP). We found that, during HCC regression, restored normal liver contained both reverted tumor hepatocytes (RFP+) and newly differentiated hepatocytes (GFP+). RNA sequencing (RNA-seq) analyses of the RFP+ and GFP+ hepatocyte populations after tumor regression confirmed the conversion of tumor cells to normal hepatocytes, as most of the genes and pathways that were deregulated in the tumor stages were found to have normal regulation in the tumor-reverted hepatocytes. Thus, our lineage-tracing studies demonstrated the potential for transformed tumor cells to revert to normal cells after suppression of expression of a primary oncogene. This observation may provide a basis for the development of a therapeutic approach targeting addicted oncogenes or oncogenic pathways.